Odour as trace evidence - Jurczyk-Romanowska, Ewa (Journal of Education Culture and Society, 2020)
There are a number of scent classification systems that typically take into account the similarities and differences in human olfactory perception, regardless of what chemical compounds cause a particular sensation. Also there is no objective, physical or chemical basis for the classification of odours, unlike eyesight or hearing. In fact, until now, scientists cannot explain, how it happens, that we can detect different scents. The present paper compares theories and classifications of human scent.